A SHORT APPROACH TO FUNCTIONALIZED HOMOCHIRAL PIPERIDINONES - Hermitage, S; Moloney, M (1994)
The preparation of homochiral lactam 4 in 5 steps from (S)-lysine is described. Convenion to bicyclic O,N-acetal 5 provides a useful template for further elaboration to highly substituted piperidinones with excellent diastereoselectivity. © 1994.